Implementasi Skrining Lansia Sederhana (SKILAS) sebagai Upaya Deteksi Dini Penurunan Kapasitas Intrinsik Lansia - Rizky Ridhayanti; Utomo Wicaksono; Akhmad Ridhani (Institut Kesehatan Suaka Insan, 2026)
The decline in intrinsic capacity among older adults may affect physical and mental functions and increase the risk of dependency in daily activities. One of the early detection efforts that can be implemented in the community is through Simple Elderly Screening (SKILAS). This community service activity aimed to implement elderly health screening using the SKILAS instrument as an early detection method for intrinsic capacity decline. The activity was conducted at Uma Kandung Elderly Home, Banjarmasin, involving 25 older adults aged over 60 years. The examinations included intrinsic capacity screening using SKILAS, blood pressure measurement, body weight assessment, random blood glucose testing, and uric acid examination. The screening results showed that all older adults experienced intrinsic capacity decline with various conditions, including cognitive decline (36%), mobility limitation (28%), malnutrition (32%), visual impairment (72%), hearing impairment (8%), and depressive symptoms (28%). In addition, 40% of the participants had abnormal blood pressure and 68% had abnormal uric acid levels. The implementation of SKILAS can support early detection of health conditions among older adults and assist in planning appropriate interventions and continuous health monitoring in the community.